Developing a Classification Structure of Organizational Problems: An Empirical Investigation - Cowan, David (Academy of Management Journal, 1990)
Many conceptual frameworks have been proposed that identify categories of organizational problems, but none have been empirically developed. In response, this study elicited examples of problems fr...